2020
DOI: 10.1155/2020/2342837
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Responses in Cardiovascular Disease: Sex-Related Differences in Nutritional and Pharmacological Interventions

Abstract: Cardiovascular diseases (CVD) represent one of the biggest causes of death globally, and their prevalence, aetiology, and outcome are related to genetic, metabolic, and environmental factors, among which sex- and age-dependent differences may play a key role. Among CVD risk factors, platelet hyperactivity deserves particular mention, as it is involved in the pathophysiology of main cardiovascular events (including stroke, myocardial infarction, and peripheral vascular injury) and is closely related to sex/age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 146 publications
0
6
0
2
Order By: Relevance
“…It was proposed that anti-platelet effect of n-3 PUFA could depend on gender. EPA seems to have more effectiveness in male while DHA in female as observed by an inverse correlation between testosterone levels and platelet aggregation after EPA administration and the observation of the higher levels of serum DHA in women independently from diet presence of DHA [85].…”
Section: The Effect Of N-3 Pufas In Platelet Functionmentioning
confidence: 92%
“…It was proposed that anti-platelet effect of n-3 PUFA could depend on gender. EPA seems to have more effectiveness in male while DHA in female as observed by an inverse correlation between testosterone levels and platelet aggregation after EPA administration and the observation of the higher levels of serum DHA in women independently from diet presence of DHA [85].…”
Section: The Effect Of N-3 Pufas In Platelet Functionmentioning
confidence: 92%
“…Platelet behaviour varies in response to a wide range of factors -ethnicity, age, nutrition status, exposure to air pollution, exercise levels, etc. (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). No two individuals' platelets are precisely the same, something that can be clearly observed in the heterogeneity of their responses to agonist and to antiplatelet agents (20)(21)(22)(23)(24), Studies using antiplatelet drugs have shown that marked differences in platelet responses may be linked to such factors, with genomic and nutrigenomic reasons postulated (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in platelet reactivity may be due to sex hormones. Both female and male platelets express receptors for 17β-estradiol as well as androgen and progesterone receptors; however, their effect on platelet function is somewhat controversial [59,60]. Platelet receptors can also regulate platelet reactivity in a sex-dependent manner.…”
Section: Platelets and Coagulationmentioning
confidence: 99%
“…Platelet activation and aggregation is mediated through the G-protein receptors PAR1 (protease activated receptor 1) and PAR4 (thrombin receptors), P2Y12 receptors (ADP receptors), and the thromboxane A2 receptor, amongst others [61]. While there is no difference in the expression of glycoprotein IIb/IIIa between sexes, women show higher receptor reactivity [59]. Moreover, healthy women and female mice have higher reactivity to PAR1 and PAR4 agonists [62], suggesting sex-dependent expression or activation of these receptors.…”
Section: Platelets and Coagulationmentioning
confidence: 99%